Türkiye'de koreografi kavramının geleneksel danslar üzerinden yeniden yorumlanması:Shaman Dans Tiyatrosu "7edi" Projesi örneği - Gümüş, Gülce Su (İTÜ Lisansüstü Eğitim Enstitüsü, 2025)
Bu çalışma, Türkiye'deki geleneksel dansların çağdaş koreografi aracılığıyla sahnede nasıl yeniden yorumlandığını araştırmaktadır. Modernleşme ve küreselleşme süreciyle birlikte geleneksel dansların sahne temsilleri değişmiş, bu danslar estetik ve anlatı açısından yeni bir biçim kazanmıştır. Ancak literatürde bu dönüşümün koreografik açıdan nasıl gerçekleştiğine dair çalışmalar sınırlıdır.Bu bağlamda, araştırma Shaman Dans Tiyatrosu tarafından sahnelenen "7EDİ" projesini inceleyerek bu boşluğu doldurmayı amaçlamaktadır.Araştırma kapsamında, nitel araştırma yöntemleri kullanılmış; literatür taraması, yaratıcı ekip ile yapılan derinlemesine görüşmeler ve performans kayıtlarının görsel analizi gerçekleştirilmiştir. "7EDİ" projesi, Türkiye'nin yedi bölgesine ait halk danslarını çağdaş koreografi teknikleriyle birleştirmekte; dans, müzik ve sahne tasarımı açısından özgün bir sentez sunmaktadır. Her bölüm için bestelenen müzikler geleneksel ezgilerden ilham almakta fakat modern orkestrasyonla yeniden kurgulanmaktadır. Elde edilen bulgular, koreografinin sadece teknik bir düzenleme değil, aynı zamanda kültürel ve bireysel ifadeyi barındıran yaratıcı bir süreç olduğunu ortaya koymaktadır. Dansçılara tanınan yorumlama özgürlüğü, geleneksel motiflerin çağdaş anlatımla yeniden doğmasını sağlamaktadır. Bu süreç, sahnede sadece bir sanat üretimi değil, aynı zamanda kültürel belleğin güncellenerek aktarılması anlamına gelmektedir.Sonuç olarak, "7EDİ" projesi; geleneksel dansların estetik, kültürel ve sanatsal değerlerini korurken, bu değerleri çağdaş bir sahne diliyle yeniden şekillendirmektedir. Koreografi, kültürel mirasın sürdürülebilirliği açısından etkili bir araç olarak ortaya çıkmakta; bu çalışma, dans sanatının kültürel kimliği geleceğe taşıyan dinamik bir ifade biçimi olduğunu göstermektedir.

Traditional dances are significant forms of expression that embody the cultural heritage of societies. The processes of modernization and globalization have transformed the stage representations of these dances, incorporating modern choreography techniques and adding new dimensions to their performance. However, there is a limited number of studies in the literature examining how traditional dances in Turkey are reinterpreted through the art of choreography. The primary aim of this study is to address this gap by analyzing how traditional dances are reconstructed on stage through choreography. Accordingly, this study focuses on the "7EDİ" project staged by Shaman Dance Theater. While investigating the fusion of traditional and contemporary dance within the project, it also explores how traditional dances are reinterpreted in the present day. The "7EDİ" performance is thematically structured around Turkey's seven regions and the seven hills of Istanbul, drawing inspiration from folk dances and music to create a contemporary narrative. By bringing together various cultural elements on stage, the performance functions as a cultural compilation, highlighting the ways in which staged works serve as curated representations of traditional heritage. The central research question of this study examines the techniques employed by the art of choreography in adapting traditional dances for the stage and the role of this process in both preserving and reproducing Turkey's cultural dance heritage. Additionally, the study investigates whether staged performances function solely as artistic expressions or also serve as cultural compilations. Ultimately, this research aims to reveal the role of choreography in the preservation and sustainability of cultural heritage.This study adopts qualitative research methods, utilizing both literature review and fieldwork-based data collection techniques. To understand how traditional dances in Turkey are integrated into contemporary performing arts, academic sources, books, and articles in the fields of dance and choreography were first examined. Research focusing on the fusion of folk dances with modern choreography provided the foundation for a broader evaluation of the artistic vision of the "7EDİ" project. This theoretical framework established the conceptual basis of the study. In the applied section of the research, in-depth interviews were conducted with the creative team of Shaman Dance Theater. One-to-one interviews were held with the project's choreographers, executive team, and coordinators. Through these discussions, comprehensive insights were gained into the creative process of "7EDİ", staging decisions, choreographic methods, and the ways in which traditional dance motifs were adapted to a contemporary stage language. Additionally, visual analyses of the "7EDİ" performance were carried out. These analyses, based on performance recordings, examined the movement language of the dance, stage design, use of music, and narrative structure. By assessing concrete examples, this approach provided an opportunity to evaluate how traditional dance elements were integrated and transformed through contemporary choreography.Through this combination of methods, the study adopts both a theoretical and practical analytical approach. The choreographic structure of the "7EDİ" project is examined from both an internal perspective (through interviews with artists and the creative team) and an external perspective (through visual analyses and literature review), ensuring a comprehensive evaluation. Furthermore, the fact that the project's choreographers are Turkish artists highlights the influence of local artistic perspectives on the choreographic process. This aspect contributes not only to the preservation of cultural heritage but also to the development of a distinctive form of expression in contemporary dance production. Ultimately, this study offers a significant perspective on how dance as an art form is represented in both national and international contexts within Turkey. The findings of this study reveal how the "7EDİ" project establishes a relationship between traditional dances and contemporary choreography. The interviews conducted and analyses performed within the scope of the research provide detailed insights into the project's choreographic methods, staging approach, and musical structure. In this context, it has been observed that "7EDİ" creates a unique synthesis between traditional and modern elements. The study identifies that folk dances from Turkey's seven regions have been restructured using modern choreography techniques. According to the choreographers, regional dance motifs have been preserved; however, during the staging process, these figures were stylized and integrated into a contemporary expressive language. Similarly, the musical structure consists entirely of original compositions, with each section's music specifically composed from scratch by Oğuzhan Balcı. The characteristic structures of local music were reinterpreted using modern orchestration techniques; rather than directly replicating folk melodies, they were reconstructed. These approaches demonstrate that the work harmonizes traditional and modern elements in an original manner, functioning as a cultural compilation both choreographically and musically. Additionally, it was found that the choreographic process allowed dancers individual expressive space, enabling movements to be reshaped through their interpretations. This finding indicates that choreography extends beyond a purely technical arrangement; rather, it is an evolving creative process enriched by the dancers' artistic contributions. Overall, the "7EDİ" project successfully integrates traditional and modern dance elements, demonstrating that staged performances can function both as cultural compilations and as effective tools for transmitting cultural memory through the medium of performance. This study has examined how the "7EDİ" project integrates traditional Turkish dances with contemporary choreography and whether the staged performances function as cultural compilations. The analyses conducted and the interviews with the project team reveal that "7EDİ" presents a unique and cohesive synthesis in terms of choreography, music, and stage design. One of the most significant findings of this study is that traditional dances in contemporary performing arts should not be viewed merely as representations of the past but as dynamic and adaptable art forms. The choreographers reinterpreted dance motifs from various regions using modern staging techniques, allowing dancers to contribute their individual expressive interpretations. This approach ensured that the choreographic process was not a static structure but rather an interactive and creative formation. It also demonstrates that choreography extends beyond an aesthetic discipline to serve as a cultural and artistic medium of expression. Additionally, choreography undergoes a historical evolution, and interviews with past and present artists provide a bridge between tradition and contemporary artistic practice. This perspective enables an examination of how choreography in Turkey has adapted to historical and societal transformations. The "7EDİ" project can thus be seen as a contemporary reflection of this historical continuity. From a musical perspective, the project was composed entirely of original pieces, deliberately avoiding the direct use of traditional folk melodies. Composer Oğuzhan Balcı reinterpreted the musical characteristics of different regions of Turkey through modern orchestration techniques, establishing a strong network of interaction between music and dance. As a result, the "7EDİ" project is not only a choreographic endeavor but also a cultural reproduction process from a musical standpoint. Another key finding is that staged performances can serve as cultural compilations. "7EDİ" brings together traditional dance and musical elements from various regions of Turkey and reinterprets them within a contemporary artistic context. This process highlights that choreography is not merely a tool for aesthetic expression but also plays an active role in preserving, transforming, and transmitting cultural heritage to future generations. Media coverage supports this view, describing "7EDİ" as an innovative performance that brings Istanbul's historical and cultural identity to the stage. Critics and artistic communities have emphasized that the project successfully bridges tradition and modernity and possesses the qualities necessary for international festival participation. In conclusion, this study has demonstrated how traditional dances can be adapted to modern performing arts through choreography and has provided significant contributions to the sustainability of cultural heritage. Projects like "7EDİ" serve as models for preserving, developing, and representing cultural heritage through artistic expression, while also holding the potential to inspire similar projects in the future.
The choreographic reinterpretation of traditional dance in Turkey: The 7edi Project by Shaman Dance Theatre
Tez (Yüksek Lisans)-- İstanbul Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2025
Keywords: geleneksel dans; traditional dance; koreografi; choreography; modern dans; modern dance; bale ve dans; ballet and dance; halk bilimi (folklor)